ANALISIS KINERJA KEUANGAN PT. JASA RAHARJA - Muh Hidayatullah; Anwar Ramli; Tenri S. P. Dipoatmodjo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine how the financial performance of PT. Jasa Raharja in 2017 to 2021. The population in this study is the company's annual financial statements, while the sample used is the company's financial statements from 2017 to 2021. The data collection technique in this study is by means of documentation, then it will be analyzed using ratios. liquidity which consists of Current Ratio, Cash Ratio and solvency ratio which consists of Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) and profitability ratio consists of Return on Assets (ROA) and Return on Equity (ROE) which then measures financial health using the Risk Based Capital method. The results of this study indicate that the liquidity ratio where the Cash Ratio is still below the standard ratio, which means the company is less able to pay its short-term obligations using existing cash, but the company is still able to pay its short-term debt using its current assets and the solvency ratio is above the standard ratio in general, which means the company's finances are quite good in meeting long-term debt and for profitability ratios where the Return on Assets is still below the standard ratio, which means the company is less efficient in managing its assets to generate profits but in terms of Return on Equity the company has been able to manage capital owned to earn a profit, while Risk Based Capital shows the company's financial performance from 2017 to 2021 is quite good.